Wishtree - Applegate, Katherine; Santoso, Charles (New York Feiwel and Friends, 2017)
"A red oak tree and a crow help their human neighbors work out their differences"--
Keywords: Toleration -- Fiction; Trees -- Fiction; Crows -- Fiction; Wishes -- Fiction; Friendship -- Fiction; Toleration -- Fiction; Trees -- Fiction; Crows -- Fiction; Wishes -- Fiction; Friendship -- Fiction